2014
DOI: 10.11648/j.ajbio.20140205.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amylase Activity in Patients with Type 2 Daibetes Mellitus

Abstract: Diabetes mellitus is a chronic metabolic disorder which is associated with hyperglycemia. It is caused by a derangement in the secretion or function of the endocrinal portion of the pancreas. There is a close anatomical and functional relationship between its exocrine and endocrine portions. The current study was designed to evaluate the changes in amylase levels in diabetic patients and study the correlation of amylase activity with chronic hyperglycemia and duration of diabetes mellitus. The results of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
3
6
0
2
Order By: Relevance
“…This finding was in agreement with results of some workers 6,11,16,17,[20][21][22] . On the contrary, some researchers found serum amylase level was significantly higher in type 2 diabetic subjects 23,24 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding was in agreement with results of some workers 6,11,16,17,[20][21][22] . On the contrary, some researchers found serum amylase level was significantly higher in type 2 diabetic subjects 23,24 .…”
Section: Discussionsupporting
confidence: 94%
“…The relationship between serum amylase and duration of disease was statistically significant.Similar finding was also made by other research workers 20 . Amylase in type 2 diabetic subjects became more severely affected in long-standing cases of diabetes mellitus 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also found by researchers, where the relationship between serum amylase and duration of diabetes was statistically significant and amylase in type 2 diabetic subjects became more severely affected in long-standing cases of diabetes mellitus indicating that measuring serum amylase levels in diabetics may be used for understanding the progress of diabetes. 15 In this study, we compared serum amylase and fasting blood sugar to correlate islet and acinar cell linkage which significantly shows low serum amylase level in type 2 diabetic patients as compared to that of healthy controls. We also found significantly higher Fasting sugar in type 2 Diabetic mellitus as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…It is upheld that the action of insulin is critical for the production of pancreatic amylase [30,31] as such the common etiology in these conditions may be depleted secretion of insulin from the pancreas [32]. Although some studies reported low amylase level in type II diabetes mellitus, attributing it to the decline in the trophic effect of insulin on the pancreatic acinar cells [33,34,35], others claimed existence of transient and acute increases (from several to ten times beyond the upper normal level) in serum amylase concentration as a result of destruction of acinar cells in the pancreas [36]. However, repeated acute pancreatitis may eventually results in exhausted acinar cells and restricted flow of enzymes from pancreas parenchyma into the circulation [37,38,39] leading to low serum amylase.…”
Section: Discussionmentioning
confidence: 99%